2007
DOI: 10.1002/hc.20299
|View full text |Cite
|
Sign up to set email alerts
|

Stabilizing effect of intramolecular lewis base toward racemization of optically active selenoxides

Abstract: 2-(Methylchalcogenomethyl)diphenyl selenoxides 1 and 2-{2 -(N,N-dimethylamino)ethyl}

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Interestingly the reaction proceeds with retention of configuration. In further studies, Shimizu and co‐workers showed the stabilizing effect of intramolecular Lewis bases toward racemization of optically active selenoxides 113…”
Section: Selenium At Higher Oxidation Stagesmentioning
confidence: 99%
“…Interestingly the reaction proceeds with retention of configuration. In further studies, Shimizu and co‐workers showed the stabilizing effect of intramolecular Lewis bases toward racemization of optically active selenoxides 113…”
Section: Selenium At Higher Oxidation Stagesmentioning
confidence: 99%
“…A similar optical resolution ( Figure 6) was applied to racemic 2-(methylchalcogenomethyl)diphenyl selenoxides 153-154 and 2-{2_-(N, N-dimethylamino)ethyl}-phenyl alkyl (or aryl) selenoxides 156-158. However, selenoxide 155 could not be resolved by this procedure [60]. Three enantiomerically pure 8-(dimethylamino)-1-aryl(alkyl)-naphthyl selenoxides 159-161 (Figure 7) were isolated by chromatographic resolution using a chiral column ((Daicel Chiralpak AS; 10 × 250 mm).…”
Section: Chromatographic and Non-classical Resolution Of Racemates Bymentioning
confidence: 99%
“…The common features that exist between the CD spectra of selenoxides 143-149 and optically active p-tolyl mesityl sulfoxide and p-tolyl 2,4,6-triisopropylphenyl sulfoxide were used to assign the absolute configuration of the dextrarotatory selenoxide enantiomers [57,58]. The relationship between the absolute configurations around a stereogenic selenium atom of 2-(methylchalcogenomethyl)diphenyl selenoxides 153-154 and 2-{2-(N,N-dimethylamino)ethyl}-phenyl alkyl (or aryl) selenoxides 156-158 and the chiroptical properties of the enantiomers of was clarified by comparing with those of sulfur analogues [60]. Earlier, the absolute configurations of the optically active chalcogen oxides 159-161 were assigned by comparison of their specific rotations and CD spectra with those of their sulfur analog [61,62].…”
Section: Absolute Configurations and Enantiomeric Excesses Of Opticalmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in the synthesis of solandelactone E ( Figure 1 b), the rearrangement tolerates a variety of functional groups. Enantioselective synthesis of chiral allylic alcohols and amines is possible when either the selenoxide is produced using a chiral oxidizing agent or a chiral ancillary group including those that stabilize the selenoxide against racemization [ 1 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%